2009
DOI: 10.1111/j.1460-2695.2009.01378.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue performance of metallic reverse‐bent joints

Abstract: A B S T R A C T Adhesively bonded lap shear joints have been investigated widely and several ideas have been proposed for improving joint strength by reducing bondline stress concentrations. These include application of adhesive fillets at the overlap ends and use of adhesive with graded properties in the overlap area. Another, less common, approach is to deform the substrates in the overlap area in order to obtain a more desirable bondline stress distribution. Previous work carried out by the authors on a num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…From the experimental results, it was found that adhesively bonded butterfly joints ( Figure 2) had a longer fatigue lifetime than those of the bonded butt joints under the same conditions. Fessel et al [3] proposed a reverse-bent joint geometry ( Figure 3) in order to improve fatigue performance of adhesively bonded joints. From their results, high improvement in fatigue performance was obtained.…”
Section: Effect Of Geometric Parametersmentioning
confidence: 99%
“…From the experimental results, it was found that adhesively bonded butterfly joints ( Figure 2) had a longer fatigue lifetime than those of the bonded butt joints under the same conditions. Fessel et al [3] proposed a reverse-bent joint geometry ( Figure 3) in order to improve fatigue performance of adhesively bonded joints. From their results, high improvement in fatigue performance was obtained.…”
Section: Effect Of Geometric Parametersmentioning
confidence: 99%
“…In general, there are two approaches for fatigue lifetime prediction; namely, the stress-life approach [22][23][24][25][26][27][28][29][30][31][32] and the fatigue crack initiation/propagation approach. [33][34][35][36][37] In the former, a series of tests under various loads is performed in order to obtain the plot of stress vs. the number of cycles to failure, which is known as the S-N curve or Wohler's curve.…”
Section: Introductionmentioning
confidence: 99%
“…An example of that is the work published by Altan et al [6], where the results suggest that fatigue strengths of adhesively-bonded butterfly joints have a longer life span than those of the bonded butt joints under the same circumstances. Fessel et al [7] have investigated the effect of a reverse-bent joint geometry for the improvement of fatigue performance of adhesively bonded joints. The results suggest, that the improvements obtained under static tests conditions can be translated to even higher benefits in fatigue.…”
Section: Introductionmentioning
confidence: 99%